Explaining the reasons for the divorce of young couples in Western Iran: A qualitative Study from the Beneficiary's point of view - Javad Yoosefi Lebni; Seyed Fahim Irandoost; Mandana Saki; Bahar Khosravi; Ahmad Ahmadi (PLoS ONE, 2026)
Divorce is an important social issue that has destructive consequences for both the individual and the family. It is a multi-dimensional and complex phenomenon that occurs under the influence of various factors, so this research was conducted to explain the reasons for divorce among young couples in the West of Iran with a qualitative approach. This research was carried out with a qualitative approach and conventional content analysis. Purposeful and snowball sampling were used to identify the participants. Semi-structured interviews were used to collect data and continued until theoretical saturation was reached. In this research, 16 key informants and 32 main participants were present. For data analysis, Graneheim and Lundman method was used. Also, to increase the quality of the research, Guba and Lincoln's four criteria were observed. 212 primary codes, 24 subcategories, and 3 categories came from the analysis of the interviews. Categories and sub-categories include 1- individual factors (sexual problems, mental-psychological disorders, spouse's behavioral characteristics, individualism, physical appearance problems, Formation of a positive understanding of divorce consequences, having defective relationships before marriage, drug use), 2- socio-cultural factors (de-tabooing of divorce, women-oriented social changes, media and social networks, lack of a suitable support system, inappropriate spouse choosing, economic challenges, modeling of divorce), 3- family factors (job's impact on family life, improper communication with spouse's family, accumulation of negative feelings in marital life, issues related to children, cheating on spouse, inefficient relationships, heterogeneity of lifestyle, violence, inability to manage challenges). The results indicate that divorce is a complex, multi-dimensional phenomenon influenced by individual, social, cultural, and family factors. Prevention requires multi-level interventions, including educating couples on sexual issues and communication skills, promoting responsible marital roles, preventing superficial marriages, reducing stigma around seeking psychological help, managing personality and lifestyle differences, guiding families on conflict resolution, and providing access to counseling and mental health services before and after marriage.